The Mevalonate Pathway Is Indispensable for Adipocyte Survival - Yu-Sheng Yeh; Huei-Fen Jheng; Mari Iwase; Minji Kim; Shinsuke Mohri; Jungin Kwon; Satoko Kawarasaki; Yongjia Li; Haruya Takahashi; Takeshi Ara; Wataru Nomura; Teruo Kawada; et al. (iScience, 2018)
Summary: The mevalonate pathway is essential for the synthesis of isoprenoids and cholesterol. Adipose tissue is known as a major site for cholesterol storage; however, the role of the local mevalonate pathway and its synthesized isoprenoids remains unclear. In this study, adipose-specific mevalonate pathway-disrupted (aKO) mice were generated through knockout of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase (HMGCR). aKO mice showed serious lipodystrophy accompanied with glucose and lipid metabolic disorders and hepatomegaly. These metabolic variations in aKO mice were dramatically reversed after fat transplantation. In addition, HMGCR-disrupted adipocytes exhibited loss of lipid accumulation and an increase of cell death, which were ameliorated by the supplementation of mevalonate and geranylgeranyl pyrophosphate but not farnesyl pyrophosphate and squalene. Finally, we found that apoptosis may be involved in adipocyte death induced by HMGCR down-regulation. Our findings indicate that the mevalonate pathway is essential for adipocytes and further suggest that this pathway is an important regulator of adipocyte turnover. : Pathophysiology; Molecular Mechanism of Behavior; Diabetology; Specialized Functions of Cells Subject Areas: Pathophysiology, Molecular Mechanism of Behavior, Diabetology, Specialized Functions of Cells